The F38-Like Group, a New Group of Caprine Mycoplasmas? - Ernϕ, H. (Acta Vet Scand, 1983)
This paper concerns the taxonomic status of the F38-like group (MacOwan), a prime determinant of contagious caprine pleuropneumonia (CCPP). Extensive biochemical and serological investigations on strain F38 are reported. Some complex serological relationships with other mycoplasma species are revealed. The results, taken in conjunction with earlier published work on geno-typic characters, lead to the conclusion that final classification of these organisms should await further comparative studies of a number of field strains with a related group of strains classified as M. capri-colum. The characterization of F38 confirms its partial relationship to the “M. mycoides group” of ovine/caprine/bovine mycoplasmas, and has also revealed a very close phenotypic relationship to the bovine mycoplasma serogroup 7, a finding of potential diagnostic and epidemiological importance.